Rethinking Palm Oil Plastic Regulations for Sustainable and Ecological Justice - Anis Mashdurohatun; Yusfandi Usman; Toni Ariadi Efendi; Purwatik, Purwatik; Istiniyati, Istiniyati (Journal of Human Rights, Culture and Legal System, 2025)
Oil Palm Plantations significantly contribute to Indonesia’s economy through agricultural production and exports. However, their development has caused environmental damage and social conflicts, leading stakeholders to resist and call for more sustainable management practices to protect both the environment and local communities. This study aims to evaluate the current regulations on Sustainable Palm Oil Plasma management to identify weaknesses that affect ecological justice and sustainability. It seeks to propose improvements based on ecological justice principles to ensure environmental protection and social fairness. The research uses a constructivist approach, collecting and descriptively analyzing data from stakeholders, supported by relevant legal theories. This research reveals three main findings. First, fundamental problems persist in palm oil plasma management, including land conflicts due to community demands for plasma plantations within company concessions and companies’ failure to fulfill legal obligations such as building plasma plantations. Second, perceptions of sustainability standards like RSPO and ISPO differ significantly between certified and uncertified farmers, with many smallholders lacking access, knowledge, and resources to comply, limiting widespread implementation. Third, recent regulatory changes under the Job Creation Law create challenges in land availability for plasma plantations, especially in regions with limited land, impacting both plantation companies and plasma farmers.